Study on the mechanical and tribological behaviour of Al/Al2O3/Gr hybrid metal matrix composite produced by powder metallurgy - Norul Amierah, Nor Zamani (2020)
In recent years, the multifunctional quality requirements of materials in automotive and aerospace industries have necessitated the development of light-weight composite materials. Among the different types of materials, aluminium (Al) is considered as one of the popular choices of the materials due to its high formability and light-weight properties. However, Al shows low wear resistance under insufficient lubricating conditions which limits their use in tribological applications. Therefore, self-lubricating materials are preferred because the solid lubricant contained in them can be automatically released during the wear process to reduce the wear. Graphite (Gr) is one of the materials which possess high lubricating characteristics. However, the limitation of graphite in adding aluminium matrix is that it significantly reduces the strength of the composite. Therefore, one solution could be to introduce a third material to the Al-Gr composite to improve the strength of the composite. Alumina (Al2O3) is one of the popularly used ceramic materials whose introduction to the aluminium can increase the mechanical strength. The most important issue of composite fabrication is to maintain the uniformity of the reinforcement particles on the metallic matrix. The mechanical strength significantly influenced by the particles homogeneity. Among the various fabrication techniques, powder metallurgy is considered to be an effective process as reinforcements uniformity can be achieved by this. Therefore, in this study, hybrid composite composed of aluminium matrix and Al2O3, Gr reinforcements has been developed by powder metallurgy technique and the effect of Al2O3 and graphite content on the mechanical and tribological behaviour of the Al/Al2O3/Gr hybrid composite has been studied. In this study, the fabrication has been carried out in two phases. In the first phase, aluminium-graphite (Al-Gr) composites with different weight percentage values of graphite were fabricated and their mechanical and wear properties were evaluated, and the optimum value of graphite was determined. After that, hybrid MMCs was fabricated by adding Al2O3 and graphite reinforcement particles to the aluminium base material. At this stage, the percentage of the graphite particles kept constant (the value provided high wear resistance) but the percentage of Al2O3 reinforcement varied in order to get the high mechanical properties. The raw powders with the desired percentage were mixed, compacted and sintered to get the hybrid composites. The fabricated samples were then prepared for microstructural characterization, mechanical and tribological tests. The microstructure showed a proper bonding and uniform distribution of the reinforcement in the Al matrix. The results revealed that all the mechanical properties, including hardness, tensile strength and flexural strength increased significantly and the tribological properties tremendously improved in the hybrid composite as compared to the pure aluminium and Al-Gr composite. Moreover, the combined effect of 10% Al2O3 and 3% Gr displayed superior performance in both the mechanical and tribological properties.